2006
DOI: 10.1080/00071660600741776
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary metabolisable energy, calcium and phosphorus on bone mineralisation, leg weakness and performance of broiler chickens

Abstract: 1. Performance, gait score (GS), tibial dyschondroplasia (TD), and tibia bone mineralisation and breaking strength were determined in 2880 male and female Ross 208 broilers fed on diets with two different concentrations of dietary metabolisable energy (ME) (11.00 or 12.00 MJ/kg) and 4 different concentrations of available phosphorus (aP) adjusted for dietary ME content (4.0, 4.5, 5.0 or 5.5 g/kg aP in starter and 3.5, 4.0, 4.5 or 5.0 g/kg aP in finisher diets containing 12.00 MJ/kg). 2. Tibia ash, calcium (Ca)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
50
2
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(58 citation statements)
references
References 26 publications
4
50
2
2
Order By: Relevance
“…In modern meat-type chickens, bone strength and development are closely linked to the expression of genetic potential for maximum lean muscle deposition (Williams et al, 2004). Overall, the results of the current study suggest that bone mineral content and bone mineral density may be more sensitive indicators of dietary Ca and P concentrations in broilers than tibia breaking strength (Venäläinen et al, 2006).…”
Section: Resultsmentioning
confidence: 58%
“…In modern meat-type chickens, bone strength and development are closely linked to the expression of genetic potential for maximum lean muscle deposition (Williams et al, 2004). Overall, the results of the current study suggest that bone mineral content and bone mineral density may be more sensitive indicators of dietary Ca and P concentrations in broilers than tibia breaking strength (Venäläinen et al, 2006).…”
Section: Resultsmentioning
confidence: 58%
“…Da Silva et al (2001b) reported 37.01% of Ca and 20.55% of P in ash from the tibiotarsus. Venäläinen et al (2006) found that the levels of ash, Ca and P in the tibiotarsus from males were higher than those in females. By contrast, Hulan et al (1985) detected lower levels in male chickens, which are similar to our findings.…”
Section: Resultsmentioning
confidence: 95%
“…Even though dietary energy and protein levels have no notable effect on tibia breaking strength (Venalainen et al, 2006), high nutrient densities may improve chicken growth and weight gain (Corzo et al, 2004;Kidd et al, 2004;Zhai et al, 2013), thereby resulting in higher load weight capacities of their leg bones. Absolute bone breaking strength is positively related to body size (Leterrier and Nys, 1992;Shim et al, 2012a, b), however, relative breaking strength, which is expressed as breaking strength per unit of BW, may decrease with increased body mass (Chen et al, 2006;Shim et al, 2012b).…”
Section: Introductionmentioning
confidence: 99%